PENGARUH E-SERVICE QUALITY TERHADAP KEPUASAN PENGGUNA APLIKASI JAMSOSTEK MOBILE (JMO) PADA PESERTA BPJS KETENAGAKERJAAN CABANG BALI DENPASAR - Kadek Tari Septyawati; Juwita Pratiwi Lukman; I Dewa Ayu Putri Wirantari (Triwikrama: Jurnal Ilmu Sosial, 2025)
E-service quality refers to services that can be accessed through websites by users, with the aim of making purchasing and distribution activities more effective and efficient. High-quality e-service quality will create value and a positive image in the eyes of users. Additionally, the higher the quality of e-service quality, the greater the increase in user satisfaction. The objective of this research is to explain the effect of e-service quality on user satisfaction of the Jamsostek Mobile Application (JMO) for BPJS Ketenagakerjaan participants at the Bali Denpasar Branch. The research method used is a quantitative approach with Simple Random Sampling technique, utilizing SPSS data from the distribution of questionnaires to 100 BPJS Ketenagakerjaan participants at the Bali Denpasar Branch. The theoretical framework used is e-service quality according to Tatik Suryani, which includes five indicators: reliability, responsiveness, trust, design, and personalization, and also the theory of Doll and Torkzadeh, which includes five indicators: content, accuracy, format, ease of use, and timeliness. The results of the study indicate a correlation of 0.766 with a strong relationship level (Sugiyono), thus Hypothesis 1 is accepted, meaning there is an effect of e-service quality on user satisfaction of the JMO application for BPJS Ketenagakerjaan participants at the Bali Denpasar Branch. The results of the simple linear regression calculation show that every 1% improvement in e-service quality at the BPJS Ketenagakerjaan Bali Denpasar Branch will lead to a 58.6% increase in user satisfaction. Based on the significance test results, the t-value of 11.779 is greater than the t-table value (1.660) with a significance level of 0.001, which means that e-service quality has a positive and significant effect on user satisfaction of the JMO application for BPJS Ketenagakerjaan participants at the Bali Denpasar Branch